THE EFFECT OF ACUPRESSURE IN IMPROVING THE QUALITY OF SLEEP IN THE ELDERLY - Ahmad Baequny; Sri Hidayati (Prodi D3 Keperawatan Tegal Poltekkes Kemenkes Semarang, 2021)
Old age is a natural process that has become human nature. Elderly is part of the process of growth and development. Humans do not suddenly grow old, but develop from infants, children, adults and eventually become old. This is very normal, and everyone can experience it. Various changes will occur when a person grows old, including changes in sleep patterns. Sleep quality is a state of sleep that a person does to increase freshness and fitness when awake. Most of the elderly, the quality of sleep changes, namely when sleep begins to shorten. These conditions can be overcome by pharmacological and non-pharmacological therapy. One of the non-pharmacological therapies is acupressure therapy which is a complementary therapy that can cure several diseases including improving sleep quality. The aim of the study was to determine the quality of acupressure in improving sleep quality in the elderly. The method in this study is a quasi-experimental design with a pre-test and post-test none equivalent control group. The number of respondents was 54 respondents who were divided into a treatment group that was given acupressure therapy and a control group. Data collection techniques using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The results of the different test with the Mann Whiteny Test obtained a p-value of 0.000 (0.05). So it can be said that pressure has a positive effect on improving sleep quality in the elderly. Acupressure can have a relaxing effect on the elderly so that it can improve the quality of sleep in the elderly. The results of this study can be used as a reference for choosing acupressure therapy to improve sleep quality in the elderly.